2012
DOI: 10.2149/tmh.2011-25
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the Improvement of Living Conditions among Neglected Populations with Trachoma

Abstract: Objective: Trachoma (Chlamydia-triggered blinding infection) provoked irreversible visual impairment in about 8 million people in 2011, and the prevalence among children with dirty faces is more than three fold that among children with clean faces. In 250 villages with a high prevalence of trachoma (Kolofata district, Far North Region, Cameroon), the lack of water for facial cleanliness was reported during trachoma awareness campaigns. The objective of this study was to determine if the lack of water was linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In Sudan, water accessibility was a possible risk factor [85], whereas it was found to be independently associated with trachoma in Ethiopia [83]. Interestingly, a study [94] in Cameroon found that the lack of a local water source was not linked to the lack of individual or community wealth (to dig wells), but it was due more to lack of social solidarity. The authors recommended that social solidarity should be added to training guides to change behaviors away from waiting for external assistance and dig their own wells.…”
Section: Face Washing and Environmental Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sudan, water accessibility was a possible risk factor [85], whereas it was found to be independently associated with trachoma in Ethiopia [83]. Interestingly, a study [94] in Cameroon found that the lack of a local water source was not linked to the lack of individual or community wealth (to dig wells), but it was due more to lack of social solidarity. The authors recommended that social solidarity should be added to training guides to change behaviors away from waiting for external assistance and dig their own wells.…”
Section: Face Washing and Environmental Improvementmentioning
confidence: 99%
“…As already discussed, in Cameroon [94], it was discovered that the communities had the means to dig wells and have water easily accessible, but it was long-accepted that the women had to walk far to carry water back to their households. Social norms can indeed inhibit the success of a trachoma program, especially when they are evident at all levels of the community, including in health settings.…”
Section: Face Washing and Environmental Improvementmentioning
confidence: 99%
“…Such interventions reinforce improved behaviors and practices, facilitate communal commitment, and incorporate barrier identification and action capacity activities at the community, group, and individual levels. Other interventions incorporate more proximally influencing social constructs (such as social solidarity) in training guides to harness mutual responsibility and trust to improve utilization of personal and common pool resources (e.g., water) [ 83 ]. While some evidence suggests well-designed interventions may be effective when implemented over a short time horizon [ 81 ], behavior change and maintenance of improved practices involves a protracted process of confronting underlying behavioral antecedents and determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery, antibiotics and spreading information on hygiene education, face washing and environmental changes are insufficient to ensure the sustainability of trachoma elimination. Trachoma recurrence should serve, without ruining good intentions as a warning not to confine strategies merely to medical approaches especially because the assets dedicated to the prevention of blindness are limited [ 4 , 63 – 65 , 86 , 87 ]. The present work should be read as a prophylactic a posteriori auto critic and trachoma recurrence warns for the urgent need to include pedagogic actions to the present elimination strategy: absence of basic education makes hygiene teaching ineffective.…”
Section: Discussionmentioning
confidence: 99%